2014
DOI: 10.1007/s10526-014-9623-6
|View full text |Cite
|
Sign up to set email alerts
|

Toxic organic acids produced in biological soil disinfestation mainly caused the suppression of Fusarium oxysporum f. sp. cubense

Abstract: Biological soil disinfestation (BSD) is an effective and environmentally friendly way to suppress soil-borne pathogens. Although it is increasingly used in USA, the Netherlands and Japan, its precise mechanism has not been well quantified so far. Quantitative real-time PCR, denaturing gradient gel electrophoresis and high performance liquid chromatography were used for investigating the role of organic acids in the mechanisms of BSD. The results showed that BSD significantly reduced the population of Fusarium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 37 publications
6
39
0
Order By: Relevance
“…In this study, the original soil pH (4.2) was very acidic and not suitable for general plant growth and microbial activity, but it increased up to 6.0 after BSD treatment. However, rather contrasting results were reported regarding the soil pH change in BSD: in some cases the soil pH was found to be reduced (Momma et al 2006;Huang et al 2015), whereas in others increasing pH was reported (Butler et al 2012;Butler et al 2014). In fact, the change of soil pH depends on the original pH in soil.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this study, the original soil pH (4.2) was very acidic and not suitable for general plant growth and microbial activity, but it increased up to 6.0 after BSD treatment. However, rather contrasting results were reported regarding the soil pH change in BSD: in some cases the soil pH was found to be reduced (Momma et al 2006;Huang et al 2015), whereas in others increasing pH was reported (Butler et al 2012;Butler et al 2014). In fact, the change of soil pH depends on the original pH in soil.…”
Section: Discussionmentioning
confidence: 94%
“…Bands indicated with numbers were excised, re-amplified, and sequenced Our molecular results illustrated that a marked indigenous soil bacterial communities shifted in all flooded and saturated soil. As we have known, flooding used to reducing fungi populations while leaving bacteria unaffected or even increasing it (Drenovsky et al 2004;Huang et al 2015). Organic amendments such as compost or manure have been illustrated that they could affect natural soil microorganisms, especially bacteria community, and provide biological control to soilborne pathogens (Bulluck et al 2002;Tiquia et al 2002;Gelsomino and Cacco 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the soil solutions were filtered using a 0.22-µm membrane filter, and the organic acids in the soil solutions were quantified using high-performance liquid chromatography (HPLC; Waters eAlliance 2695, USA), according to the method described by Huang et al (2015b) The column used was XDB-C18 (4.6 × 250 mm, Agilent, USA), and the standards for the organic acids were purchased from Sigma (USA).…”
Section: Detection Of Toxic Organic Acidsmentioning
confidence: 99%
“…Secondly, anaerobic microbial fermentation of organic matter can result in the production of organic compounds such as volatile fatty acids (VFAs) that accumulate due to the physical barrier of the plastic tarp. VFAs may accumulate to levels that result in a decrease in soil pH and increase in toxicity to soil biota and weed seeds (Achmon et al, 2017;Gamliel and Stapleton, 1997;Huang et al, 2015a;Katase et al, 2009). Thirdly, microbiota may directly affect pest organisms through competition, such as between beneficial fungi and pathogenic fungi, or infection, such as microbial degradation of the seed coat of weed seeds (Huang et al, 2015b;Rokhbakhsh-Zamin et al, 2011).…”
Section: Soil Biosolarization (Sbs) Can Be a Sustainable Soil Pest Comentioning
confidence: 99%